Prevalence of overweight/obesity in South Asia: A narrative review - Avivar Awasthi; Akhila Bhandarkar Panduranga; Aditya Deshpande (Clinical Epidemiology and Global Health, 2023)
Introduction: Overweight (ov) and obesity (ob) are conditions associated with excess adipose tissue mass. Overweight and obese (ov/ob) individuals are at an increased risk for chronic complications like diabetes mellitus, cardiovascular disease, liver disease, malignancies, sleep apnoea, osteoarthritis, urinary incontinence, and psychosocial issues. The prevalence of ov/ob is increasing globally and in South Asia. This review provides an overview of prevalence of ov/ob in South Asia in adults and children 0–5 years of age. Methods: Data were retrieved from literature search including all national surveys published up to 1st January 2023, for South Asian countries (Afghanistan, Bangladesh, Bhutan, India, Maldives, Myanmar, Nepal, Pakistan, Sri Lanka). Specifically, national surveys conducted within the last 10 years were included. Results: The prevalence of ov/ob in adults and children 0–5 years of age ranged from 22.4 to 52.4%, and 1.3–7.6%, respectively. There was a higher prevalence seen in women, urban population, and higher socioeconomic status. Conclusion: The prevalence of ov/ob in South Asia is high and it may be even higher if Asian BMI cut-offs are applied to the surveyed population. Preventive strategies need to be tailored to the unique characteristics of ov/ob in South Asia.